2012
DOI: 10.1038/leu.2012.117
|View full text |Cite
|
Sign up to set email alerts
|

Expansion of bone marrow neutrophils following G-CSF administration in mice results in osteolineage cell apoptosis and mobilization of hematopoietic stem and progenitor cells

Abstract: Proliferation and differentiation of hematopoietic stem/progenitor cells (HSPC) within bone marrow (BM) niches are regulated by adhesion molecules and cytokines produced by mesenchymal stem/progenitor cells (MPC) and osteoblasts (OB). HSPCs that egresses to peripheral blood are widely used for transplant and granulocyte-colony stimulating factor_(G-CSF) is used clinically to induce mobilization. The mechanisms, through which G-CSF regulates HSPC trafficking however, are not completely understood. Herein we sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 45 publications
0
49
0
Order By: Relevance
“…In addition, G-CSF was shown to promote ROS production in neutrophils and administration of ROS inhibitors along with G-CSF reduced BM osteoblast apoptosis in addition to a reduction in stem and progenitor cell mobilization (91). This study suggests that ROS generated by neutrophils after G-CSF disturbed stem and progenitor cell adhesion to BM stromal cells, as it promoted osteoblast apoptosis (91). However, ROS also affect HSCs directly as a signaling molecule that promotes activation of HSC differentiation and enhanced migration.…”
Section: Fig 5 Elevated Ros Levels In Hscs and Mesenchymal Stromal mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, G-CSF was shown to promote ROS production in neutrophils and administration of ROS inhibitors along with G-CSF reduced BM osteoblast apoptosis in addition to a reduction in stem and progenitor cell mobilization (91). This study suggests that ROS generated by neutrophils after G-CSF disturbed stem and progenitor cell adhesion to BM stromal cells, as it promoted osteoblast apoptosis (91). However, ROS also affect HSCs directly as a signaling molecule that promotes activation of HSC differentiation and enhanced migration.…”
Section: Fig 5 Elevated Ros Levels In Hscs and Mesenchymal Stromal mentioning
confidence: 99%
“…In addition, high levels of ROS secreted in the vicinity of BM stromal cells were suggested to promote osteoblast apoptosis by playing a role in G-CSF-induced stem cell mobilization (91).…”
Section: Ros Mediates Proliferation and Differentiation Of Bm Mesenchmentioning
confidence: 99%
“…Granulocyte and monocyte macrophage cells originate from granulocyte macrophage hematopoietic progenitor cells, and the number of granulocyte macrophage colonies can influence the proliferative capacity of hematopoietic progenitor cells as well as immune function to some extent (Singh et al, 2012). Recent studies have shown that the Wnt signaling pathway, as an important regulator of hematopoietic stem/progenitor cells, plays an important role in the hematopoietic system (Staal et al, 2010;Ichii et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Neutrophils have also been implicated in mediating apoptosis and reduction in CXCL12 production in BM osteolineage stromal cells during G-CSF mobilization, reportedly via a reactive oxygen species (ROS)-dependent mechanism which can be partially abrogated with antioxidant N-acetyl cysteine treatment [17]. As G-CSF has been shown to ramp up ROS activity in HSPCs via the c-Met/ mTOR/FOXO3 signalling axis [25], it is plausible that elevated ROS produced by neutrophils during G-CSF mobilization contributes to the general heightened ROS levels in HSPCs and their subsequent egress from the BM.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies over the decades have demonstrated that neutrophil depletion such as induced by anti-Gr-1 antibody administration or by homozygous deletion of the Csf3r gene encoding the G-CSF receptor, severely hampered HSPC mobilization in response to G-CSF, cyclophosphamide, IL-8 or GROβ [14,[16][17][18]. As the main biological response to G-CSF administration in vivo is a pronounced neutrophilia, while anti-Gr1 administration or Csf3r gene deletion leads to a profound neutropenia, this led to the view that neutrophils play an important role in HSPC mobilization in response to these agents [19].…”
Section: Introductionmentioning
confidence: 99%